2013
DOI: 10.1186/1478-811x-11-60
|View full text |Cite
|
Sign up to set email alerts
|

Early innate immunity determines outcome of Mycobacterium tuberculosis pulmonary infection in rabbits

Abstract: BackgroundPulmonary infection of humans by Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), results in active disease in 5-10% of individuals, while asymptomatic latent Mtb infection (LTBI) is established in the remainder. The host immune responses that determine this differential outcome following Mtb infection are not fully understood. Using a rabbit model of pulmonary TB, we have shown that infection with the Mtb clinical isolate HN878 (a hyper-virulent W-Beijing lineage strain) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 56 publications
4
79
1
Order By: Relevance
“…Neutrophil abundance in the lung alveoli immediately following Mtb implantation directly correlates with virulence of the Mtb strains employed [80]. Frequencies of neutrophils in the blood of exposed individuals inversely correlate with risk of TB [81], suggesting a protective role of neutrophils.…”
Section: Early Lesions and Immune Events In Pulmonary Tbmentioning
confidence: 98%
“…Neutrophil abundance in the lung alveoli immediately following Mtb implantation directly correlates with virulence of the Mtb strains employed [80]. Frequencies of neutrophils in the blood of exposed individuals inversely correlate with risk of TB [81], suggesting a protective role of neutrophils.…”
Section: Early Lesions and Immune Events In Pulmonary Tbmentioning
confidence: 98%
“…Prior to the onset of acquired immunity, the lungs of experimentallyinfected susceptible rabbits contained 20-to 30-fold more Mtb organisms than those of resistant rabbits (Dannenberg and Rook, 1994) and a more recent study in rabbits suggested that the ultimate outcome of pulmonary Mtb infection is significantly influenced by the differential regulation of the innate immune response and associated gene expression as early as 3 h post infection (Subbian et al, 2013). Variation in these innate responses may reflect the antibacterial effectiveness of myriad components within the host immune armoury such as pathogen recognition by cell receptors, phagocytosis and the production of intra-and extracellular immunomodulatory compounds including cytokines.…”
Section: Introductionmentioning
confidence: 97%
“…The log2-transformed transcript levels from uninfected, wild type-infected or mutant-infected mice brain (n = 3 per group) was further analyzed by Partek Genomics Suite (Partek, St.Louis, MO) for statistical analysis and to identify significantly differentially expressed genes (SDEG) in the infected group, relative to the uninfected animals. The normalized RNA-Seq data from each group (n = 3) were averaged and analyzed by one-way ANOVA with equal variance for significance [48]. To identify SDEG, the log2 ratio between uninfected and wild type-or the mutantinfected transcript levels was further screened by applying an unadjusted false discovery rate (FDR) of 5% (q value ≤ 0.05).…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
“…Gene ontology analysis was performed by interrogating the SDEG generated in our studies with the IPA knowledgebase as described [48]. To improve the stringency, we included only mouse database from IPA for the network/pathway analysis.…”
Section: Network/pathway Analysismentioning
confidence: 99%